1999
DOI: 10.1023/a:1018700126364
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Evaluated psychosocial differences between youth receiving mental health services in Community Mental Health Centers (CMHCs; n = 79) as compared to youth receiving services from a program operating in 10 Baltimore schools (n = 186). Racial and gender differences were shown, with more African American youth and females in the School than CMHC sample. Multivariate analyses that controlled for these racial and gender differences failed to reveal significant effects, indicating comparable functioning on measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Few studies have examined the effectiveness of school-based centers despite their wide proliferation (Rones and Hoagwood 2000) and those that have been evaluated have shown access to children, but little involvement from parents and few child behavioral changes (e.g., Armbruster and Lichtman 1999;Catron et al 1998). For example, Weist et al (1999) found that school-based mental health centers were more likely to reach children without any prior service history, relative to a community-based clinic, but there were no further differences in client characteristics or outcomes. Furthermore, a national survey (Foster et al 2005) indicates that most school-based centers are oriented toward pull-out services with the individual child (i.e., assessment, crisis intervention, individual counseling, and case management), which are resource intensive and contrary to the goal of keeping children in their primary learning environment (the classroom).…”
Section: School Mental Health In Poor Communitiesmentioning
confidence: 97%
“…Few studies have examined the effectiveness of school-based centers despite their wide proliferation (Rones and Hoagwood 2000) and those that have been evaluated have shown access to children, but little involvement from parents and few child behavioral changes (e.g., Armbruster and Lichtman 1999;Catron et al 1998). For example, Weist et al (1999) found that school-based mental health centers were more likely to reach children without any prior service history, relative to a community-based clinic, but there were no further differences in client characteristics or outcomes. Furthermore, a national survey (Foster et al 2005) indicates that most school-based centers are oriented toward pull-out services with the individual child (i.e., assessment, crisis intervention, individual counseling, and case management), which are resource intensive and contrary to the goal of keeping children in their primary learning environment (the classroom).…”
Section: School Mental Health In Poor Communitiesmentioning
confidence: 97%
“…Progress in the development of these expanded SMH services has been facilitated by a number of state and federal initiatives including support for national centers to promote this expanded model (Adelman et al, 1999), and leadership shown by jurisdictions in doing the same (Weist, Paternite, Wheatley-Rowe, & Gall, 2009). Progress was also facilitated by early studies documenting the benefits of SMH including improved access to care (Catron, Harris, & Weiss, 1998), increased ability to implement prevention (Elias, Gager, & Leon, 1997), enhanced early identification/intervention (Weist et al, 1999), and reduced stigma of services (Nabors & Reynolds, 2000).…”
Section: Smh Programs and Servicesmentioning
confidence: 99%
“…Importantly, there is evidence that students presenting less observable problems, such as those associated with depression, anxiety, and/or the experience of trauma, are less likely to be identified (Gresham & Kern, 2004; Weist, Myers, Hastings, Ghuman, & Han, 1999) and, therefore, less likely to receive more intensive and indicated Tier 2 (targeted intervention) or Tier 3 (intensive, individual intervention) supports within the MTSS (Bradshaw, Buckley, & Ialongo, 2008). Externalizing behaviors are typically highly interactive and social.…”
Section: Systems Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of school-based mental health programs has been well-documented (Burns and Hoagwood 2004; Hoagwood and Burns 2005; Kazdin 2005; Stephan et al 2007). School-based mental health services have been shown to enhance access to other services (Cappella et al 2011; Weist et al 1999), assist in reducing the stigma of seeking help from formal sources (Nabors and Reynolds 2000), promote generalization and maintenance of treatment gains (Evans 1999), improve school climate by increasing the perceptions of support available to students and teachers (Bruns et al 2004; Walrath et al 2004), and promote a natural, ecologically grounded approach to helping children and families (Atkins et al 2003; Weist et al 1999). However, despite the availability of mental health services in most schools, youth with mental health problems (especially ADHD, depression) still face difficulties in accessing them (Foster et al 2005; Nabors and Reynolds 2000; USDHHS 2001).…”
Section: Introductionmentioning
confidence: 99%